Pharmaceutico-Analytical standardization of amavatari rasa - A herbo-mineral formulation - Sonam Sagar Bhinde; Biswajyoti J Patgiri (Wolters Kluwer Medknow Publications, 2023)
Introduction: Amavatari Rasa (AR) (mercury-containing herbo-mineral formulation), widely used in the management of Amavata (rheumatoid arthritis) has been being manufactured by many pharmaceutical companies in India for long. However, till today, the standard manufacturing process (SMP) for this formulation is not available, and hence, the present study was carried out to set the SMP of AR along with its quality control parameters. Methods: Pharmaceutical procedures such as Shodhana (pre-processing) of Parada (mercury), Gandhaka (sulfur), Chitraka (Plambago zeylanica Linn.), and Guggulu (Commiphora wightii Arn.); preparation of lime water, Triphla Kwatha (decoction) and AR were carried out at Rasa shastra and Bhaishajya Kalpana Department of ITRA, Jamnagar. Physicochemical parameters, high-performance thin-layer chromatography (HPTLC), and inductively coupled plasma atomic emission spectroscopy (ICP-AES) were carried out at the pharmaceutical chemistry Lab, ITRA, Jamnagar and Sophisticated Analytical Instrument Facility, IIT Powai, Mumbai respectively. Results: Average of 54.33 g of castor oil was required for 354.33g of AR. Mean ± standard deviation (SD) of pH, loss on drying, ash value, acid insoluble ash, water soluble extractive, and alcohol soluble extractive of AR was 3.77 ± 0.20, 6.29 ± 0.41%w/w, 5.46 ± 0.72%w/w, 0.40 ± 0.15%w/w, 23.2 ± 5.15%w/w and 30.13 ± 7.19%w/w, respectively. HPTLC study showed 4 peaks in 254 nm and 5 peaks in 366 nm ultraviolet lights. AR contains 7.38% mercury, 0.0031% arsenic, and 0.0032% lead. Conclusion: The adopted method for preparation of AR was convenient to replicate and hence can be considered SMP. Results of physicochemical parameters, HPTLC, and ICP-AES of this study could be used as quality parameters for Amavatari Rasa prepared by this method.